Chitosan oligosaccharide induces resistance to Tobacco mosaic virus in Arabidopsis via the salicylic acid-mediated signalling pathway - Jia, Xiaochen (Sci Rep, 2016)
Chitosan is one of the most abundant carbohydrate biopolymers in the world, and chitosan oligosaccharide (COS), which is prepared from chitosan, is a plant immunity regulator. The present study aimed to validate the effect of COS on inducing resistance to tobacco mosaic virus (TMV) in Arabidopsis and to investigate the potential defence-related signalling pathways involved. Optimal conditions for the induction of TMV resistance in Arabidopsis were COS pretreatment at 50 mg/L for 1 day prior to inoculation with TMV. Multilevel indices, including phenotype data, and TMV coat protein expression, revealed that COS induced TMV resistance in wild-type and jasmonic acid pathway- deficient (jar1) Arabidopsis plants, but not in salicylic acid pathway deficient (NahG) Arabidopsis plants. Quantitative-PCR and analysis of phytohormone levels confirmed that COS pretreatment enhanced the expression of the defence-related gene PR1, which is a marker of salicylic acid signalling pathway, and increased the amount of salicylic acid in WT and jar1, but not in NahG plants. Taken together, these results confirm that COS induces TMV resistance in Arabidopsis via activation of the salicylic acid signalling pathway.